Findings of a major comparative study on litigation funding and costs - Hodges, C; Vogenauer, S (2010)
This policy brief, written by Dr Christopher Hodges and Professor Stefan Vogenauer of Oxford University, is published as costs and funding are assuming far greater importance as keys to evaluating and providing access to justice. The findings were drawn upon by Lord Justice Jackson in his influential Costs Review which recommended moving to American style contingency fees, a recommendation that is widely expected to be implemented by the UK coalition government. The policy brief addresses the problem of maintaining fair and equal access to justice for all, whilst controlling cost and delay, a problem of particular relevance as governments across Europe are set to impose significant cuts in public expenditure as a consequence of the current economic climate. Using data supplied by leading practitioners across the thirty-five jurisdictions, the study looks at nine case studies of categories of claim, and conducts a comparative analysis of the range of approaches taken to administering them, before setting out possible alternative approaches.